2013
DOI: 10.1186/1742-2094-10-140
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the inflammatory transcription factor nuclear factor interleukin-6 during inflammatory and psychological stress in the brain

Abstract: BackgroundThe transcription factor nuclear factor interleukin 6 (NF-IL6) is known to be activated by various inflammatory stimuli in the brain. Interestingly, we recently detected NF-IL6-activation within the hypothalamus-pituitary-adrenal (HPA)-axis of rats after systemic lipopolysaccharide (LPS)-injection. Thus, the aim of the present study was to investigate whether NF-IL6 is activated during either, inflammatory, or psychological stress in the rat brain.MethodsRats were challenged with either the inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 85 publications
4
37
0
Order By: Relevance
“…Our study is one of few works investigating the recruitment of circulating leukocytes to the CNS following psychological distress [8,40] and the first one to suggest the AP as a possible route of entry for leukocytes, which indicates that the AP plays an important role during immune responses to distress. Considering the above-mentioned pieces of evidence with our results, we can support the theory that there is only a semantic difference between immunological stimuli such as antigens and stressors [53,54,55]. …”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our study is one of few works investigating the recruitment of circulating leukocytes to the CNS following psychological distress [8,40] and the first one to suggest the AP as a possible route of entry for leukocytes, which indicates that the AP plays an important role during immune responses to distress. Considering the above-mentioned pieces of evidence with our results, we can support the theory that there is only a semantic difference between immunological stimuli such as antigens and stressors [53,54,55]. …”
Section: Discussionsupporting
confidence: 70%
“…LPS injection [14], HIV dementia [52] and autoimmune diseases of the CNS [16]. Recently, it has also been demonstrated that inflammatory LPS stimulation as well as psychological stress can trigger the activation of inflammatory transcription factors in different cell types of the brain [53]. Our study is one of few works investigating the recruitment of circulating leukocytes to the CNS following psychological distress [8,40] and the first one to suggest the AP as a possible route of entry for leukocytes, which indicates that the AP plays an important role during immune responses to distress.…”
Section: Discussionmentioning
confidence: 99%
“…Cortes-Canteli et al, 2008), for example induced by psy-884 chological stress, can activate NF-IL6(Fuchs et al, 2013). Thus, as885 opposed to STAT3, NF-IL6 represents a broad and useful but rather886 unspecific activation marker that will be applicable for a variety of 887 future research questions.888 We further analyzed potential alterations in the immune cell 889 mediated immune-to-brain communication and observed lower 890 LPS-induced neutrophil recruitment to the brain inKO compared 891 to WT at the 8 h time point most likely due to reduced CXCL1-892 expression, a neutrophil specific chemokine.…”
mentioning
confidence: 95%
“…Brain structures were identified 220 using ''The mouse brain in stereotaxic coordinates'' (Paxinos 221 and Franklin, 2001 Cellbiology, JLU Gießen, Germany, (Blahser, 1988); rabbit-anti-239 CD163, dilution 1:1000, sc-33560; goat-anti-COX2, dilution 240 1:2000, sc-1747; rabbit-anti-NF-IL6, dilution 1:5000, sc-150; rab-241 bit-anti-STAT3, dilution 1:3000, sc-482, all from Santa Cruz 242 Biotechnology Inc., Dallas, USA; rat-anti-7/4, dilution 1:500, 243 MCA771G, ABD Serotec, Puchheim, Germany) were diluted in 244 blocking solution and sections were incubated for 20-22 h at 4°C 245 (RT for 7/4-antibody). Specificity of the respective antibodies has 246 been tested previously (Damm et al, 2011;Fuchs et al, 2013;247 Rummel et al, 2010247 Rummel et al, , 2008247 Rummel et al, , 2006. After three further washing 248 steps, sections were incubated with the secondary antibodies Corticosterone and IL-10 plasma levels were measured in blood 305 plasma using mouse specific enzyme-linked immunosorbent of all cytokines with no effect of genotype for pro-IL-1b ( The cellular communication pathway to the brain was investi-563 gated by detecting markers for neutrophil granulocytes (7/4) and (Fig.…”
mentioning
confidence: 99%
“…Various immune cells have been shown to produce hormones and neuropeptides, including ACTH (Ottaviani, Franchini, & Genedani, 1999), endorphins (Morch & Pedersen, 1995), enkephalin ( Jankovic & Radulovic, 1992;Wybran, 1985), prolactin (Gala, 1991;Yu-Lee, 1997, growth hormone (Gala, 1991;Meazza, Pagani, Travaglino, & Bozzola, 2004), catecholamines (Elenkov, 2007), and acetylcholine (Hosoi & Nomura, 2004), and the release of various neurotransmitters in immune system organs is triggered by nerve impulses from the central nervous system (CNS) to peripheral tissue (Pacheco, Riquelme, & Kalergis, 2010;Qiu, Peng, & Wang, 1996). In contrast, cytokines, such as interleukin-6, normally produced by immune cells, have been shown to be synthesized by and secreted from anterior pituitary cells when stimulated by the bacterial endotoxin, lipopolysaccharide (LPS), a model compound which mimics bacterial infection (Fuchs, Damm, Gerstberger, Roth, & Rummel, 2013).…”
Section: Brain-immune Interactions: Induction Of Neuroinflammation Bymentioning
confidence: 96%